« On n’est pas des cow-boys » - Mathieu Baudrin; Benoît Dauguet; Dalia Deias; Benjamin Raimbault (Revue d'anthropologie des connaissances)
The controversy concerning shale gas exploitation is hereby analyzed from the point of view of the oil industry. This article aims to reconnect this controversy within the long time-frame of hydrocarbons in France. We wanted to expand from the analysis of the anti-shale gas mobilization by focusing more on the pro-shale front, following the Jacob law vote. We highlighted the arenas where this controversy has been debated and how those arenas and the debating actors reconfigured the interpretation of this public issue. We wanted to analyze in detail this framing process with particular emphasis on the importance of the scientific and technical dimensions of the tools used in such operation.